2014
DOI: 10.1177/1049732314548879
|View full text |Cite
|
Sign up to set email alerts
|

Adapters, Strugglers, and Case Managers

Abstract: Although family home care problems are frequently described in the health care literature, the ways in which families and other informal caregivers manage those problems are not often addressed. We conducted a descriptive analysis of interviews in which spouses caring for a partner with Alzheimer’s or Parkinson’s disease were asked to describe difficult home care problems and how they managed those problems. Analysis of these interviews indicated three recurring management styles. Adapters told stories about a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
29
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 33 publications
3
29
0
4
Order By: Relevance
“…Caregiver burden and caregiver communication suggest an association with patient/caregiver acceptability of serious and terminal illness. Similar findings have recently demonstrated that caregiver burden is most influenced by the caregiver's management style rather than the demands of care . Patient–caregiver dyads who buffer and feel buffered by their partner, despite their intention to help, often experience less satisfaction in their relationship and poorer mental health .…”
Section: Discussionsupporting
confidence: 70%
“…Caregiver burden and caregiver communication suggest an association with patient/caregiver acceptability of serious and terminal illness. Similar findings have recently demonstrated that caregiver burden is most influenced by the caregiver's management style rather than the demands of care . Patient–caregiver dyads who buffer and feel buffered by their partner, despite their intention to help, often experience less satisfaction in their relationship and poorer mental health .…”
Section: Discussionsupporting
confidence: 70%
“…The stress brought on by the simultaneous management of paid and unpaid work, the financial toll of purchasing supplies and equipment, the lack of supports and informational resources available, and the physical demands of providing hands‐on care, among numerous other factors, all contribute to caregiver burden (Bruhn & Rebach , Davis et al . , Williams et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…RESULTSCaregivers on average were 66.8 years old (SD = 12.5; range = 33-95); approximately 27% (n = 68) were African American, and half were caring for a spouse (n = 131). Of a possible 23 behavioral problems that a PLWD may exhibit, caregivers reported an average of 9.4 (SD = 3.8; range,[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Upset over these problems was moderate with an average score of 52.9 (SD = 30.2; range, 7-153).…”
mentioning
confidence: 99%